Comparison of health-related quality of life in different polycystic ovary syndrome phenotypes: A cross-sectional study. (April 2022) - Li, Xiaoyan; Cui, Tiaoxia; Song, Xueru; Tian, Wenyan; Lin, Yuezhi; Zhang, Huiying
Highlights: Patients with PCOS were divided into refined and specific phenotypes. Find the main factors affecting the HRQoL of different PCOS phenotypes. Provide targeted guidance for psychological treatment and long-term management of PCOS. Abstract: Objective: The goal of this research was to evaluate the Health-Related Quality of Life (HRQoL) of Chinese women with varying phenotypes of Polycystic Ovary Syndrome (PCOS) and related factors in order to guide clinical treatment. Methods: We employed a cross-sectional design that included 221 women with an initial diagnosis of PCOS at the Department of Obstetrics and Gynecology, Tianjin Medical University General Hospital. All subjects were stratified, according to the Rotterdam criteria, into three sub-cohorts: phenotype A ( n  = 100), phenotype B ( n  = 60), and phenotype D ( n  = 61). All patients completed the Modified Polycystic Ovary Syndrome Health Related Quality of Life Questionnaire (MPCOSQ). Results: The three PCOS phenotypes showed no obvious differences in terms of the overall mean MPCOSQ score. However, patients in phenotype D exhibited markedly elevated weight, hirsutism, and acne scores, as compared to phenotypes A and B (p＜0.05). Among all phenotypes, A and B exhibited the worst weight-related HRQoL (3.58 ± 1.89, 3.42 ± 1.99). In contrast, phenotype D displayed the worst emotional disturbance (3.74 ± 1.25), followed by infertility (3.86 ± 1.99). According to the multiple linear regression analysis, worse HRQoL in Phenotypes A and B was significantly associated with excess body weight (Beta = -0.387, -0.626, p＜0.001), hirsutism (Beta = -0.309, -0.269p＜0.01), and abnormal menstruation (Beta = -0.283, -0.304, p＜0.01). In contrast, there was no marked association between HRQoL and hirsutism in Phenotype D. Conclusion: Personalized treatment and management must be provided, based on various factors that influence HRQoL among the three PCOS phenotypes. Based on our analysis, the interventions that greatly improve HRQoL of PCOS patients are significant weight loss, combined with anti-androgen administration for phenotypes A and B, and fertility enhancement, combined with menstruation regulation, for phenotype D.